(untitled) (Revista Interação Interdisciplinar (ISSN: 2526-9550), 2021)
The COVID-19 outbreak infected millions of people around the globe, forcing the people stay home. The new daily life became indoor shopping and the retailers had to adapt to this new reality, causing a high demand for the logistics. This paper presents the willingness of a post-pandemic medium-sized city consumers to adopt new modalities of delivery: reception boxes, delivery drones and crowdsourcing logistics. Through a survey with closed questions applied online to 401 people, the results indicated that younger people tend to buy more online than older ones. People with a higher education level also buys more online. It was possible to affirm that the popular opinion was positive towards experimenting these innovations and the presented results corroborates with the related research.